Artificial Intelligence and Higher Education: Dancing with the AI Tiger. - Rubic, Louise (Journal of the Australian Traditional Medicine Society)
The most recent ATMS Educators Forum delved into the implications of large language models (LLMs) within the higher education landscape, exploring our engagement with artificial intelligence (AI) as both a transformative ally and a formidable challenge. Inspired by the discourse in preparation for the event, the forum presentation titled 'Artificial Intelligence: Dancing with the Tiger', was developed to describe a brief AI history and acknowledged the nuanced dance with ChatGPT, an emblematic figure of chat-based generative AI. During the forum a word cloud survey resulted in two dominating perceptions of AI: potential and scary. These perceptions made way for insightful discussions from educators and students, concluding that AI is already pervasive in education and that navigating through its potential perils and harnessing its promises to foster a more inclusive and dynamic learning environment is becoming essential.